Cell lineage tracing in the retina: Could material transfer distort conclusions?. Issue 1 (13th July 2017) - Boudreau‐Pinsonneault, Camille; Cayouette, Michel
Abstract : Recent studies reported the transfer of fluorescent labels between grafted and host cells after transplantation of photoreceptor precursor cells in the mouse retina. While clearly impacting the interpretation of transplantation studies in the retina, the potential impact of material transfer in other experimental paradigms using cell‐specific labels remains uncertain. Here, we briefly review the evidence supporting material transfer in transplantation studies and discuss whether it might influence retinal cell lineage tracing experiments in developmental and regeneration studies. We also propose ways to control for the possible confounding occurrence of label exchange in such experiments. Developmental Dynamics 247:10–17, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Evidence of material transfer in retinal transplantation is reviewed. Possible confounding effects of label transfer in cell lineage tracing are discussed. Different ways to control for possible label transfer in cell lineage tracing studies are proposed.